2013
DOI: 10.1017/s0047279413000470
|View full text |Cite
|
Sign up to set email alerts
|

Asset Poverty in Urban China: A Study Using the 2002 Chinese Household Income Project

Abstract: Defining asset poverty as insufficiency of assets to satisfy household basic needs for a limited period of time, the study examines asset-poverty rates in urban China using the 2002 survey data from the Chinese Household Income Project (CHIP). We find that asset-poverty rates in urban China are lower than those of developed countries, in part due to Chinese households' strong commitment to precautionary savings and the low poverty standards. However, the liquid asset-poverty rate is five times that of the inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 30 publications
(94 reference statements)
1
3
0
Order By: Relevance
“…Previous studies have indicated that being a member of the communist party in China is positively correlated with beneficial social and economic outcomes (e.g., better paying jobs, higher household income, and wealth accumulation; Dickson & Rublee, 2000;Huang et al, 2013;Li, Liu, Zhang, & Ma 2007;Meng, 2007). Our study extended the literature by showing that communist party membership not only benefits household income and wealth but also affects the use of formal credit, a valuable resource that is restrained in the Chinese financial market.…”
Section: Low Prevalence Of Formal Credit Usesupporting
confidence: 70%
See 1 more Smart Citation
“…Previous studies have indicated that being a member of the communist party in China is positively correlated with beneficial social and economic outcomes (e.g., better paying jobs, higher household income, and wealth accumulation; Dickson & Rublee, 2000;Huang et al, 2013;Li, Liu, Zhang, & Ma 2007;Meng, 2007). Our study extended the literature by showing that communist party membership not only benefits household income and wealth but also affects the use of formal credit, a valuable resource that is restrained in the Chinese financial market.…”
Section: Low Prevalence Of Formal Credit Usesupporting
confidence: 70%
“…With information on participants' owned assets and credit, we created three continuous variables to measure household asset holding. In using this approach, we followed studies on asset poverty (Brandolini, Magri, & Smeeding, 2010;Haveman & Wolff, 2005;Huang et al, 2013). The first of the three asset-holding variables was net worth.…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…Similar patterns of wealth poverty appear in other countries. Using survey data from the Chinese Household Income project, Huang et al (2013) and Yang et al (2019) found that asset poverty is far more prevalent than income poverty among households in China. Based on data from the Luxembourg Wealth study and similar definitions to those used by Caner and Wolff (2004), Brandolini et al ( 2010) estimated wealth poverty rates in Canada, Finland, Germany, Italy, Norway, Sweden, the U.K., and the U.S. finding that asset poverty rates are higher than income poverty rates in every country regardless of the liquidity of the wealth measure.…”
Section: Empirical Evidence On the Wealth Dimension Of Povertymentioning
confidence: 99%
“…This rate was 2.6 times higher than the official income poverty rate of 9.2%. Since then, the methodology has been replicated several times for the USA (Aratani & Chau, ; Caner & Wolff, ; Leonard & Di, ; Rank & Hirschl, ; Ratcliffe & Zhang, ), and has been used to estimate asset poverty in Korea (Kim & Kim, ), China (Huang et al, ), and a subset of Western developed countries (Brandolini et al, ). Comparable methods have also been used to estimate asset poverty in Belgium (Bosch, ), in Australia and Germany (Headey, Krause, & Wagner, ), and in the UK and Spain (Azpitarte, ).…”
Section: Introductionmentioning
confidence: 99%